Buccal mucosa or penile skin for substitution urethroplasty: A systematic review and meta-analysis - Gopal Sharma; Sneha Sharma; Kalpesh Parmar (Indian Journal of Urology, 2020)
Penile skin (PSG) and the buccal mucosa (BMGs) are the most commonly used grafts for substitution urethroplasty. The aim of this study was to compare the success rates of substitution urethroplasty using either of these grafts. We systematically searched PubMed/Medline, EMBASE, Scopus and Web of science to identify studies comparing the two types of graft urethroplasties. Search strategy was based on Patient, Intervention, Control and Outcome guidelines. Studies reporting data on success of PSG versus BMG within the same manuscript were included. Standard Preferred reporting Items for Systematic reviews and Metaanalysis guidelines were followed while conducting this review and study protocol was registered with PROSPERO in priori (CRD42018114258). Sixteen studies, including 5 prospective and 11 retrospective studies, with a total of 1406 (896 BMG and 510 PSG) patients were included in the final analysis. In the overall analysis, BMG had significantly higher success rate (83.7% vs. 76.1%, P ≤ 0.0001). Duration of followup was heterogeneous across the studies, ranging from 15.9 to 201 months. Comparing the five studies where the data on duration of follow up was available, BMG showed a significantly higher success rate compared to PSG (90% vs. 80.4%; P = 0.02). In the subgroup of patients with bulbar urethral strictures, BMG urethroplasty had significantly higher success rate (87.4% vs. 78.0%; P = 0.0001). From the results of this study, buccal mucosa may appear to be a better choice, however, the data is still immature and a properly conducted randomized controlled trial with an adequate duration of followup is required.